Efeitos cardiorrespiratórios, musculares e funcionais da quimioterapia de indução em pacientes com neoplasias hematológicas - Rodrigues, Bianca Soares (2023)
Introduction: Patients with hematological neoplasms undergoing induction chemotherapy (IC) suffer from severe fatigue and low physical and functional aptitude. As several factors can be determinant or associated with functional decline, further studies are needed to investigate multifactorial issues and possible pathophysiological mechanisms in this population. Objective: to analyze the influence of the disease and IC on cardiorespiratory, muscular and functional variables in patients with hematological neoplasms. Method: It is characterized as a cross-sectional study in which patients with hematological neoplasms, admitted to a public hospital for the first cycle of chemotherapy, were evaluated before and after this exposure regarding functional capacity, respiratory muscle strength, muscular architecture, handgrip strength (HGS), lower limb resistance, fatigue and quality of life. Assessments were carried out respectively using the 6-minute walk test (6MWT), manovacuometry, muscle ultrasound (US), handgrip dynamometry, sit-to-stand test (STS), FACIT-F scale and EORTC QLQ C-30 Quality of Life Questionnaire. Results: Of the 18 patients recruited, 8 completed the pre and post IC assessment protocol. Regarding muscular architecture, there was a reduction in the cross-sectional area (CSA) of the rectus femoris (RF) by 24.3% and in the pennation angle (PA) of the RF by 12.7% after IC. Improvement in emotional function was observed after the first cycle. Furthermore, inspiratory and expiratory muscle strength, HGS, lower limb resistance, functional capacity and social function scale were below predicted values. Conclusion: IC impairs muscular architecture and improves emotional function right after the first cycle. Muscular, emotional, social function and functional capacity are reduced in relation to predicted values, but appear to maintain a standard and do not worsen at the end of induction. The delay between the diagnostic investigation and the start of treatment in the public network may interfere with the worsening of the functional conditions in which patients begin IC. Early assessment of these variables and before treatment-related toxicities occur may result in better clinical development, functionality and less social impact in patients with hematological cancer.